2022
DOI: 10.1136/bmjgh-2022-010260
|View full text |Cite
|
Sign up to set email alerts
|

The autonomy of public health facilities in decentralised contexts: insights from applying a complexity lens in Kenya

Abstract: The financing of public health facilities influences their performance. A key feature that defines health facility financing is the degree of financial autonomy. Understanding the factors that influence public health facility financial autonomy is pertinent to developing strategies to addressing challenges that arise from constrained autonomy. In this paper, we apply a complexity lens to draw on a body of research that we have conducted in Kenya over the past decade, from the onset of devolution reforms, to un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Although this problem is not restricted to devolved settings, subnational governments may have a strong interest in limiting facility autonomy to maximise their revenues. 18 …”
Section: Ineffective Subnational Purchasing Of Health Servicesmentioning
confidence: 99%
“…Although this problem is not restricted to devolved settings, subnational governments may have a strong interest in limiting facility autonomy to maximise their revenues. 18 …”
Section: Ineffective Subnational Purchasing Of Health Servicesmentioning
confidence: 99%
“…Regional U5M rates in Kenya in 2014 ranged from 42 to 82 per 1000 live births 6. This underlines the need for local data to inform ongoing programmatic efforts, especially in decentralised health systems like Kenya where allocative health decisions are made at the county level 8…”
Section: Introductionmentioning
confidence: 99%
“…6 This underlines the need for local data to inform ongoing programmatic efforts, especially in decentralised health systems like Kenya where allocative health decisions are made at the county level. 8 Migori County is situated in western Kenya in the former Nyanza province and has a population of approximately 1.1 million. 9 The economy primarily relies on subsistence farming with fishing prevalent in areas that border Lake Victoria.…”
Section: Introductionmentioning
confidence: 99%
“…This is a reform approach that involves reducing direct government control over public hospitals and increasing their exposure to market and market like incentives [1,2]. The financing of public health facilities influences their performance with degree of financial autonomy being a key feature that defines health facility financing [3]. Financial autonomy refers to the level of control and influence that health facility managers have, to mobilize, allocate and spend financial resources [4].…”
Section: Introductionmentioning
confidence: 99%
“…While decentralization is often expected to enhance financial autonomy at the local levels, evidence has shown that this is not always the case [4]. For instance, in Kenya decentralization resulted in a counterintuitive recentralization of autonomy over financial management from the public health facility level to the local government level and therefore, understanding the factors that influence public health facility financial autonomy is pertinent to developing strategies to addressing prevailing challenges [3].…”
Section: Introductionmentioning
confidence: 99%